The Study of Bio-Fuel Generation and Characteristics Analysis from Jatropha, Karanja and Styrax Officinalis L Seed Cakes - Deshmukh, Minal; Marathe, A. B.; Bhutada, Dinesh (Distributed Generation & Alternative Energy Journal, 2021)
Because of their high oil content in the kernel and ability to reduce green- house gas emissions, non-edible Jatropha, Karanja, and Styrax officinalis L seeds are primarily used in biodiesel production. Outstanding demand for biodiesel, as well as a huge amount of waste, is growing year after year. As a result, the research analysis includes the hydrolysis, saccharification, and fermentation of non-edible de-oiled cakes derived from the aforementioned plants. The study research includes the generation of bio-ethanol from non- edible cakes, as well as the de-oiled seed kernel, which is incubated at 200◦C, 25◦C, 30◦C, 35◦C, with pH 4, 5, 6, 7, and a holding time of 24 hours to produce the solid fuel. The compound cake is then fermented for 72 hours at 28◦C with Saccharomyces cerevisiae with a PH range of 5 to 6, and the substrate is autoclaved for 5 minutes at 15 psi pressure. Furthermore, this research study performed centrifuge harvesting at 10,000 rpm for 10 minutes at 4◦C. The study’s findings demonstrate the time-related conversion of sugar (DNSA) and alcohol production (potassium dichromate) treatment, which outperforms the prior acid hydrolysis process.